Perancangan Maskot Lembah Kecubung Untuk Meningkatkan Awareness Publik - Aimmatus Solikhah; Bayu Setiawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Desa Penanggungan, Kecamatan Trawas, Kabupaten Mojokerto, Provinsi Jawa Timur is a village that has great potential to become a tourist destination because of its beautiful natural scenery. For this reason, the village government and local residents built the Wisata Agro Lembah Kecubung which is still in the development stage. Therefore, as a tourist attraction that has just started and is not yet known to many people, supporting tools are needed to attract public attention to the existence of the Lembah Kecubung, one of which is by using character or mascot designs. This mascot design method begins with data collection through surveys and interviews. Then it continues with the creative process which refers to Brown's design thought theory, including the emphatize, define, ideate, prototype and test stages. The result of this design is an alternative mascot design inspired by the shape of the Javanese Serak owl which is designed using farmer attributes, such as hats, towels and rice scythes.